Envelope-specific antibody response in HIV-2 infection - Marcelino, Jose Maria (2015)
Objective: To examine the unspecific and envelope-specific IgA and IgG responses in acute and chronic HIV-2 infection. Methods: Twenty-eight chronically infected adults and two children with perinatal infection were studied. Total plasma concentrations of. - Fundacao para a Ciencia e Tecnologia [POCTI/ESP/48045]. - The present work was supported by Fundacao para a Ciencia e Tecnologia (project POCTI/ESP/48045). Jose Marcelino is the recipient of a PhD scholarship from Fundacao para a Ciencia e Tecnologia (FCT), Portugal. The Instituto Portugues do Sangue (IPS), Port